a culture of safety in construction projects in Palestine - fawzi naalwa; WALEED ABDUL RAZEQ; SADDAM SALAMEH (My University, 2014)
Safety is a vital aspect in construction projects, in West Bank a lot of projects Suffer from problems in safety, or lacks safety. Many risks face contractors and owner, employees or property. Safety in project may lead to success or failure of the project. Applying safety rules in projects will lead to reducing the risks associated with construction. The aspects that will be covered in this project will be:    Definition of safety and safety management, safety management in project life cycle, safety management process and practices. Analysis of  the operating environment of the construction industry in West Bank, investigation of the safety rules and criteria that must be applied in construction projects, and the effects or benefits of applying or not applying this rule.     There are few data about safety in the construction industry in Palestine. The main aim of the study is to benchmark and strengthen the safety in the construction projects in Palestine, to assess workers experiences and perceptions of safety at construction sites in the West Bank, and to reduce the risks resulting from not applying the safety measures in the projects and the consequent losses.   To achieve this objective, the following methodology will be followed:    Applying desk research including, books, previous comparative studies. Identifying some of the risks that may occur in the project s in different cities examine all the risk ratio of these risks on several cities, Recommending  some measures necessary for the application of safety culture on the construction projects.    This project is about a very important issue that has been approached before and many projects and researches were done about safety management. But this project will be done about safety management in constructions projects in Palestine, taking into account the special circumstances of Palestine.